GAYA BAHASA DALAM NOVEL JEJAK LANGKAH KARYA PRAMOEDYA ANANTA TOER - Tressyalina, Fatrina Eliza, Yasnur Asri, (Universitas Negeri Padang, 2017)
This study aims to describe the type and function of the language style contained in the novel Jejak Langkah by Prameodya Ananta Toer. This research is a type of qualitative research using descriptive method. The style of language described there are two groups, namely rhetorical style and figurative style of language. Three types of data contained in this research, the style of rhetorical language, figurative language style and language style functions in the novel Jejak Langkah by Pramoedya Ananta Toer. Data is collected by reading the novel Jejak Langkah repeatedly, identifying, classifying and inventorying the language styles contained in the novel Footsteps. The findings of the research, in Pramoedya Ananta Toer's Jejak Langkah novel, found 602 styles of language as well as the language styles contained in the novel Tramps of Pramoedya Ananta Toer found in five types of fungsi style.Kata kunci: gaya bahasa, novel